Sosialisasi Budidaya Maggot Black Soldier Fly untuk Mengatasi Limbah Pertanian di Desa Pogalan, Kecamatan Pakis - Fitriana Heni Tiali Susanti; Oktavio Hoki Pratama; Rakha Dharmawan Tsani; Dio Setiawan; Dias Luky Ardiansyah; Kurniataka Dicky Agyari; Arsy Nisa Fadhilah; Velly Dwita Sekarputri; Lintang Kinanthi Deandra Alyya Songda; Ifa Nur Inayah; Raahma Wulan Idayanti (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
Pogalan Village in Pakis District, Central Java, is known as a horticultural agricultural center, with abundant vegetable production every year. However, behind this potential, this village faces a serious problem in the form of large amounts of organic waste generated from harvest residue and agricultural processing. Waste that is not managed properly has the potential to cause environmental pollution, reduce the village's aesthetics, and become a source of disease spread. To address these problems, the Tidar University Community Service Program (KKN-50) Team conducted a socialization activity for Black Soldier Fly (BSF) maggot cultivation as an environmentally friendly and economically valuable organic waste management solution. BSF maggots have been proven to decompose organic waste by up to 60% in a short time and produce useful by-products, such as dried maggots as high-protein animal feed and kasgot (used maggots) that can be used as organic fertilizer. The activity was held on July 31, 2025, at the Pogalan Village Hall, with the main participants being PKK mothers as agents of change at the household and community levels. The implementation method included initial observation of the village's potential and problems, creation of a maggot cultivation prototype, theoretical material outreach, and live demonstrations of the cultivation process. The material provided covered the BSF life cycle, cultivation techniques, selection of growing media, maggot population management, and utilization of cultivation products. The results of the activity showed high enthusiasm from participants, as reflected in the many questions and discussions during the training session, as well as their increased understanding of the benefits and techniques of maggot cultivation.